Trabalho, família e ser social: elos que unem a centralidade do trabalho às relações familiares - Paula, Renato Francisco dos Santos (2005)
The present thesis approaches family and work understood as element that constitute and are constituted by social totality. It is supported bu Marxist tradition rescued by Gyorgy Lukacs (1885-1971), wich consists in the study of the social being